(untitled) (Islas, 2023)
Introduction: The place of lexicography among the scientific disciplines is currently under discussion. With this study we propose to review its evolution from the first half of the 20th century to the present day and to defend its autonomous nature. Methods: A critical review of the main contributions in the Hispanic field of metalexicography is the cornerstone of our study, which is critical-descriptive in nature. Results: The numerous advances that, especially since the second half of the 20th century, have taken place in theoretical lexicography, in addition to the concretion of several theories of lexicography, make up the theoretical scaffolding that serves us to justify that lexicography or, at least, metalexicography is today a fully scientific autonomous discipline. Conclusions: The delimitation of the scope of metalexicography, the genesis of several general theories of lexicography between 1940 and the last decade, in addition to the establishment of a series of principles of lexicographic definition are arguments that allow us to affirm that lexicography is an independent science of linguistics.